Estimated Glomerular Filtration Rate in Pediatric Patients with β-Thalassemia Major: A Single-Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Vania Ilmi Basri; Husni; Desiekawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Patients with β-thalassemia major can experience impaired kidney function. Impaired kidney function can occur without symptoms and before serious manifestations appear, so early markers are needed to detect kidney damage. Estimated glomerular filtration rate (eGFR) is a calculation to detect early impairment of kidney function and is widely accepted as an indicator in determining overall kidney function. This study aims to determine the estimated glomerular filtration rate in pediatric patients with β-thalassemia major. Methods: This research is a descriptive research. Data was taken from pediatric patients with β-thalassemia major who received routine transfusions at the pediatric polyclinic of Dr. M. Djamil General Hospital Padang from January 1st – July 31st 2023. Patients underwent hematology examination, serum ferritin, serum creatinine, and estimated glomerular filtration rate calculations using the Schwartz formula. Results: A total of 55 children met the research criteria, consisting of 27 boys (49%) and 28 girls (51%). The median serum creatinine level was 0.5 (0.3-0.8) mg/dL with a range with a mean estimated glomerular filtration rate of 167 mL/minute/1.73m2. Conclusion: Glomerular hyperfiltration occurs in the majority of β-thalassemia major patients, but a decrease in